2003
DOI: 10.4049/jimmunol.170.3.1383
|View full text |Cite
|
Sign up to set email alerts
|

Suppressor of Cytokine Signaling 1 Inhibits IL-10-Mediated Immune Responses

Abstract: IL-10 has proved to be a key cytokine in regulating inflammatory responses by controlling the production and function of various other cytokines. The suppressor of cytokine signaling (SOCS) gene products are a family of cytoplasmic molecules that are essential mediators for negatively regulating cytokine signaling. It has been previously shown that IL-10 induced SOCS3 expression and that forced constitutive expression of SOCS3 inhibits IL-10/STAT3 activation and LPS-induced macrophage activation. In this repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(116 citation statements)
references
References 41 publications
6
109
0
1
Order By: Relevance
“…In contrast, in our experiments, Stat3 function was suppressed, possibly secondary to heterodimerization with high levels of activated Stat1, but levels of Stat3 tyrosine phosphorylation were preserved. The intact activation of Jak1 and Stat3 by IL-10 in IFN-␥-activated macrophages is consistent with previous reports showing that IL-10 signaling can be relatively resistant to inhibition by SOCS proteins in a cell type-dependent manner (37,38). Our results showing that IFN-␥ regulates the balance of Stat1 and Stat3 activation by IL-10, together with the results from Biron and O'Shea and colleagues (36) demonstrating differential activation of Stat1 and Stat4 by IFN-␣␤ over the time course of a viral infection in vivo, support the notion that dynamic regulation of the activation of different STATs by cytokines plays an important role in determining the activity of pleiotropic cytokines.…”
Section: Discussionsupporting
confidence: 78%
“…In contrast, in our experiments, Stat3 function was suppressed, possibly secondary to heterodimerization with high levels of activated Stat1, but levels of Stat3 tyrosine phosphorylation were preserved. The intact activation of Jak1 and Stat3 by IL-10 in IFN-␥-activated macrophages is consistent with previous reports showing that IL-10 signaling can be relatively resistant to inhibition by SOCS proteins in a cell type-dependent manner (37,38). Our results showing that IFN-␥ regulates the balance of Stat1 and Stat3 activation by IL-10, together with the results from Biron and O'Shea and colleagues (36) demonstrating differential activation of Stat1 and Stat4 by IFN-␣␤ over the time course of a viral infection in vivo, support the notion that dynamic regulation of the activation of different STATs by cytokines plays an important role in determining the activity of pleiotropic cytokines.…”
Section: Discussionsupporting
confidence: 78%
“…Reports indicate that overexpression of the SOCS-3 gene promotes IL-10 production, and that IL-10 can induce SOCS1 and SOCS-3 expressions. We also observed that overexpression of SOCS1 can promote IL-10 expression of DCs (32,33). These findings attracted speculation that IL-10 very likely plays a pivotal role in the differentiation process of regulatory DCs.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies report discovered that IL-10 rapidly induces SOCS3 in a STAT3-dependent manner [40,41] . Because SOSC3 can negatively regulate responses to different activating cytokines and bacterial products, it is speculated that the anti-inflammatory action of IL-10 is due to induction of SOCS3 [42] .…”
Section: Irradiation Induced Expression Of Socs3 and Regulated Expresmentioning
confidence: 99%